Analisis Strategi Pengembangan Bisnis Pada Usaha Kecil Menengah (Studi Pada Usaha Kue Tradisional Arando di Medan) - Endah Sulistyaningrum (Jurnal Niaga & Bisnis (e-journal), 2015)
This study aims to determine the strategies used by businesses Arando Traditional Cake and Business development of Arando Traditional Cake over the last 3 years. The method used is descriptive qualitative method. Data were obtained from observations, interviews and literature study. Analysis using SWOT analysis. Informants in this study consisted of key informants and key informants. Determination of informants using purposive sampling and accidental sampling. The results show that the strategy has been used by businesses in Medan Arando Traditional Cake is to maintain the quality and taste of the product followed with affordable pricing. Traditional Cake Business Development Arando during the last 3 years of a development in terms of promotion by using social media such as Facebook and Instagram. In addition, variations in product launches Arando latest cake, caramel cake is now available in store . The analysis showed that the appropriate strategy to support business growth Arando is an aggressive strategy of creating a strategy that uses force to take advantage of opportunities.Keywords : Business Strategy, SWOT Analysis